Does speculum lubricant affect liquid‐based Papanicolaou test adequacy?. Issue 3 (19th November 2013) - Lin, Stephanie N.; Taylor, Jolyn; Alperstein, Susan; Hoda, Rana; Holcomb, Kevin
<x xml:space="preserve">Abstract</x> BACKGROUND There is a paucity of data on the effect of vaginal lubricants on specimen adequacy in the era of liquid‐based Papanicolaou (Pap) tests. Current manufacturer recommendations advise against the use of lubricants, especially those that contain carbomers or carbopol polymers. There is, however, no conclusive evidence to support this recommendation. Moreover, the data that does exist is conflicting. METHODS Retrospective review was performed of all liquid‐based Pap tests collected between January 2010 and March 2012 by the Gynecologic Oncology division at a single hospital. Specimen adequacy was compared for vaginal and cervical specimens that were collected with and without a lubricant. Results were also compared for specimens collected with lubricants that did or did not contain carbomers. RESULTS There was no significant difference in specimen adequacy for cervical or vaginal Pap test specimens collected with a water‐soluble lubricant not containing carbomers, compared to those collected without a lubricant. There was, however, a significantly higher rate of insufficient specimens when a water‐soluble lubricant containing carbomers was used. This difference was most pronounced for vaginal Pap tests (26.9% versus 1.2%, OR = 30.3, 95% CI = 16.6‐55.1, P < .0001). CONCLUSIONS Lubricants containing carbomers should be avoided when collecting liquid‐based Pap tests because they can significantly decrease specimen adequacy. Lubricants that do not contain these substances do not significantly affect specimen adequacy. If there is an unusual increase in unsatisfactory Pap tests, the cytology laboratory should notify clinicians and work with them to determine the cause. Cancer (Cancer Cytopathol) 2014;122:221–226. © 2013 American Cancer Society.